Association between marijuana use and electrocardiographic abnormalities by middle age: the Coronary Artery Risk Development in Young Adults (CARDIA) study. (9th August 2020) - Jakob, Julian; Stalder, Odile; Syrogiannouli, Lamprini; Pletcher, Mark J.; Vittinghoff, Eric; Ning, Hongyan; Tal, Kali; Rana, Jamal S.; Sidney, Stephen; Lloyd‐Jones, Donald M.; Auer, Reto
Abstract: Aims: To evaluate the prevalence of electrocardiogram (ECG) abnormalities in marijuana users as an indirect measure of subclinical cardiovascular disease (CVD). Design: Longitudinal and cross‐sectional secondary data analysis from the CARDIA (Coronary Artery Risk Development in Young Adults) study. Setting: Four communities in the United States. Participants: A total of 2585 participants from the 5115 black and white men and women recruited at age 18–30 years in 1985 to 1986 in CARDIA. Measurements: ECG abnormalities coded as minor and major abnormalities with the Minnesota code of electrocardiographic findings at year 20. Self‐reported current (past 30 days) and computed cumulative life‐time marijuana use (one 'marijuana‐year' corresponds to 365 days of use) through assessments every 2–5 years. We fitted logistic regression models adjusting for sex, race, center, education, age, tobacco smoking, physical activity, alcohol use and body mass index. Findings: Among the 2585 participants with an ECG at year 20, mean age was 46, 57% were women, 45% were black; 83% had past exposure to marijuana and 11% were using marijuana currently. One hundred and seventy‐three participants (7%) had major abnormalities and 944 (37%) had minor abnormalities. Comparing current with never use in multivariable‐adjusted models, the odds ratio (OR) for major ECG abnormalities was 0.60 [95% confidence interval (CI) = 0.32–1.15] and for minor ECG abnormalities 1.21 (95% CI = 0.87–1.68). Results did not change after stratifying by sex and race. Cumulative marijuana use was not associated with ECG abnormalities. Conclusion: In a middle‐aged US population, life‐time cumulative and occasional current marijuana use were not associated with increases in electrocardiogram abnormalities. This adds to the growing body of evidence that occasional marijuana use and cardiovascular disease events and markers of subclinical atherosclerosis are not associated.